2008
DOI: 10.4012/dmj.27.765
|View full text |Cite
|
Sign up to set email alerts
|

UV-VIS spectra and photoinitiation behaviors of acylphosphine oxide and bisacylphosphine oxide derivatives in unfilled, light-cured dental resins

Abstract: The aims of this study were to investigate the photoinitiation behaviors of acylphosphine oxide (APO) and bisacylphosphine oxide (BAPO) derivatives in comparison to D,L-camphorquinone (CQ)/tertiary amine (EDAB) system. Fifty six kinds of experimental unfilled, light-cured resins were prepared using APO, BAPO, CQ, EDAB, resin monomers, and adhesive monomers. The measurements of ultraviolet-visible (UV-VIS) spectroscopy, photopolymerization with differential scanning calorimeter (photo-DSC) and degree of convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 12 publications
4
54
0
2
Order By: Relevance
“…Therefore, it was suggested that upon light irradiation, free radicals were generated by two concurrent and parallel mechanisms in CQ-APO: α-cleavage and hydrogen abstraction reactions. 4,5) , like the photoinitiation mechanism of acylphosphine oxides 7) . In the case of CQ-APO with an electron donating agent such as a tertiary amine, it is also noteworthy that after α-diketone [-C(=O)-C(=O)-] of CQ-APO absorbed the energy of visible rays to convert into an excited state (CQ*-APO), α-hydrogen of tertiary amine would then donate CQ*-APO to form CQ*-APO-amine exciplex (excited state complex).…”
Section: Uv-vis Spectral Behaviors Of Cq-apo Cq and Tmdpomentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it was suggested that upon light irradiation, free radicals were generated by two concurrent and parallel mechanisms in CQ-APO: α-cleavage and hydrogen abstraction reactions. 4,5) , like the photoinitiation mechanism of acylphosphine oxides 7) . In the case of CQ-APO with an electron donating agent such as a tertiary amine, it is also noteworthy that after α-diketone [-C(=O)-C(=O)-] of CQ-APO absorbed the energy of visible rays to convert into an excited state (CQ*-APO), α-hydrogen of tertiary amine would then donate CQ*-APO to form CQ*-APO-amine exciplex (excited state complex).…”
Section: Uv-vis Spectral Behaviors Of Cq-apo Cq and Tmdpomentioning
confidence: 99%
“…In the case of CQ-APO with an electron donating agent such as a tertiary amine, it is also noteworthy that after α-diketone [-C(=O)-C(=O)-] of CQ-APO absorbed the energy of visible rays to convert into an excited state (CQ*-APO), α-hydrogen of tertiary amine would then donate CQ*-APO to form CQ*-APO-amine exciplex (excited state complex). The latter was subsequently decomposed to CQ-APO ketyl radical and free radicals derived from tertiary amines, like the photoinitiation mechanism of camphorquinone 7) . However, unlike an inactivated CQ-ketyl radica l7) , the CQ-APO ketyl radical might undergo C-P cleavage to form free radicals (Fig.…”
Section: Uv-vis Spectral Behaviors Of Cq-apo Cq and Tmdpomentioning
confidence: 99%
See 3 more Smart Citations